UPAYA MENINGKATKAN PRESTASI BELAJAR SISWA DENGAN PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING TERHADAP PEMBELAJARAN IPA SISWA KELAS VI SD NEGERI 020 TEMBILAHAN HILIR - Mardianis Mardianis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to find out how the achievement, understanding and mastery of science subjects after theapplication of problem solving learning and knowing the influence of problem solving learning method inimproving students' achievement and understanding of science lesson material after applied problem solvinglearning. The method used to increase learning activity is through problem solving method. This study wasconducted in class VI of SD Negeri 020 Tembilahan Hilir. The study was conducted in May 2016 with 23students. The result of this research concludes that learning with problem solving method has a positive impactin improving student's learning achievement which is marked by the improvement of students' learning masteryin every cycle, that is cycle I (56,52%) and cycle II (89,96%). Application of problem solving method has apositive influence, that is can improve student's learning motivation; learning method of problem solving has apositive impact on the understanding of the subject matter being taught, whereby by this method students areforced to solve problems related to the subject matter being taught.